2009
DOI: 10.1007/s00586-009-1060-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adjacent segment disease after lumbar fusion

Abstract: The incidence of adjacent segment problems after lumbar fusion has been found to vary, and risk factors for these problems have not been precisely verified, especially based on structural changes determined by magnetic resonance imaging. The purpose of this retrospective clinical study was to describe the incidence and clinical features of adjacent segment disease (ASD) after lumbar fusion and to determine its risk factors. We assessed the incidence of ASD in patients who underwent lumbar or lumbosacral fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
199
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(205 citation statements)
references
References 29 publications
1
199
2
3
Order By: Relevance
“…However, the usefulness of the procedure remains uncertain. It is known that solid fusion can influence the biomechanics of the spine and thus may cause degeneration, leading within 10 years of the operation to adjacent segment alterations and symptoms in up to 40 % of patients [3][4][5][6][7][8]. Degenerative changes in discs, facet joints and ligaments can cause disc prolapses, stenosis and degenerative spondylolisthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the usefulness of the procedure remains uncertain. It is known that solid fusion can influence the biomechanics of the spine and thus may cause degeneration, leading within 10 years of the operation to adjacent segment alterations and symptoms in up to 40 % of patients [3][4][5][6][7][8]. Degenerative changes in discs, facet joints and ligaments can cause disc prolapses, stenosis and degenerative spondylolisthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Battie et al [5] found that adjacent segment degeneration after fusion was a natural process that was not related to the fusion surgery. However, some other researchers conducted in vitro mechanical studies and found that lumbar fusion may induce abnormal intradiscal pressure and too much movement at the adjacent spinal levels, resulting in adjacent segment degeneration [6]. Therefore, it appears that ASD may be partially caused by the abnormal discal stresses distribution that arised by lumbar fusion and fixation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical relevance of ASD is low in the great majority of cases [2,[6][7][8]. Cauda equina syndrome is a very unusual onset of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…ASD is likely a consequence of normal degenerative progression influenced by altered biomechanics related to fusion [1,2,4,6,[13][14][15][16]. Fusion length, stiffness of instrumentation, posterior interbody fusion, and sagittal balance could be important parameters linked to ASD [2][3][4]6].…”
Section: Discussionmentioning
confidence: 99%